Student Voice in Personal Tutoring - Raby, Alison (Frontiers in Education, 2020)
This study focuses on student voices within personal tutoring at the University of Lincoln. It asks the questions: What do students think of their personal tutoring experience at the University of Lincoln? Do students see themselves as partners with their tutors? What language do they use to describe this relationship? How does the experience of international students compare with home students? Before completing the investigation, a literature review was conducted in order to help answer the above questions. Literature around the student voice in personal tutoring and engagement in tutoring was investigated to help to understand the personal tutoring relationship and the idea of partnership. Personal tutoring generally was researched, and personal tutoring of international students. The study began with an online survey, open to any students within the university, around their experiences of personal tutoring. Subsequently, one-to-one semi-structured interviews were conducted with 30 students across the four colleges of the university, with three of the four colleges being well-represented. It was found in the interviews that a good proportion of students would seek advice from their personal tutors first about a range of issues. However, a number of students maintained that they would approach the most relevant person directly. The majority of students experienced a positive relationship with their personal tutors. However, a small number found their tutor distant or unfamiliar. Group tutorials were largely found to be useful spaces for students to express their voices. Differences were identified in the experience of international students, most saying that they would contact friends, and relatives before using their personal tutor or university services for personal issues. Some noted that tutors went above and beyond what would be expected of a personal tutor. In conclusion, it is recommended that all staff receive training on referrals, and tutors responsible for international students should receive more training, particularly around helping students transitioning into the culture of the UK. The findings of the study indicate that personal tutors could play an important role in enabling students' voices to be heard and could be a vital source of help for international students transitioning into UK Higher Education.